Pop-Up Delamination of Electrodes in Solid-State Batteries. Issue 3 (6th March 2018) - Guo, Kai; Tamirisa, Prabhakar A.; Sheldon, Brian W.; Xiao, Xingcheng; Gao, Huajian
Abstract : Interfacial delamination can be detrimental to the cycle life of solid-state batteries. Here, we investigate a pop-up delamination mechanism by which a delaminated electrode pops up from its underlying current collector against a solid electrolyte. It is shown that the delamination can proceed via the spreading of a single pop-up or multiple pop-up blisters along the interface, and that there is a threshold Li concentration below which the pop-up delamination cannot occur even in the presence of a large initial defect along the interface. The energy release rate associated with delamination is determined for different moduli and thicknesses of the electrolyte. The present study provides a theoretical foundation to understand and prevent pop-up interfacial delamination in solid-state batteries.